SMOKING CESSATION – A “MUST HAVE” OF GOOD ORAL HEALTH STATUS - Antigona Trofor; Ramona Miron (Romanian Journal of Medical and Dental Education, 2014)
Chronic tobacco consumption is a disease per se and it is defined as nicotine dependence. Furthermore, smoking is known to induce many diseases such as cancers, cardiovascular disorders, chronic obstructive lung diseases, etc., to seriously affect pregnancy and delivery in smokers as well as infant and foetus, to be an unaesthetic condition and to generally damage anyone actively or passively exposed to this major risk factor. From dental medicine practitioner’s point of view, we can say for sure smoking has a negative impact on oral health and on evolution towards healing of oral pathology in smokers. By such perspectives, we propose an analysis of best pattern to make dentists willing to involve in smoking cessation interventions. Therefore, best examples to enable dentists to preserve smoke-free patients and to avoid negative consequences of tobacco on oral health status are looked for. Despite scientific evidence of incriminatory effects of tobacco on human health, tobacco products continue to be legally sold everywhere in the world. Dentists have the opportunity to periodically assist smoking patients in their practice. So, if current or former smokers, such occasions should be frutified towards smoking abstinence or to create motivation to maintain smoke-free status in never smokers. Dentists should routinely evaluate smoking status of their patients, assess willingness to quit smoking and send motivated smokers to specialized smoking cessation centres which are now available in many cities in Romania. Swiss expertize on motivational interview to stop smoking is quoted, by giving example a team of Swiss dentists that have successfully implemented in their country a model of dentists units team trained to specifically assist smokers to quit in dentistry